Benchmarking of key performance factors in textile industry effluent treatment processes for enhanced environmental remediation - M. U. Shakeel; S. Z. J. Zaidi; A. Ahmad; A. A.M. Abahussain; M. H. Nazir (Scientific Reports)
Abstract This article presents a comprehensive benchmarking analysis of merit performance factors in the Effluent Treatment Plants (ETP) of the textile industry. The study aims to identify and evaluate key factors that contribute to the efficient operation and performance of ETPs. The performance of ETP was analyzed by valuable data gained from figures of PH, Dissolved oxygen, Dissolved solids, Suspended solids, Density, COD and BOD. The technical trends showed the deviations in the working conditions of Effluent Treatment Plant by variation in temperature. This variation is achieved by varying the settling time of wastewater in the sedimentation tank during the working process. The required dosing, plant efficiency and economic factors were taken into account. The Plant efficiency was determined to be 83.5% at normal conditions of water entering at temperature of 30°C and pressure of 1 atm along with addition of coagulants and flocculants in the wastewater. While the efficiency of the ETP plant was calculated about 88% using a Compact photometer at elevated conditions of temperature such as > 45°C, while at other temperatures the efficiency decreases significantly due to several reasons. The operating time of water treatment was decreased due to the variations in temperature of wastewater while other conditions kept constant like pressure, flow rates of water and chemicals (Polyacrylamide and Polymeric Ferric Sulfate). The usage of coagulants and flocculants at optimum conditions has been discussed in this study.